The development of the volume of trade exchange between the Russian Federation and Turkey and its impact on the economic growth of the two countries during the period (1989 - 2015) - Shanaz Hakeem Mohammed; Dilan Ghafour Salih (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
TheTraderelation between Russia and Turkey is privately and publicly crucial in terms of Economic, Industrial, Trade, Investment, Service. The importance of this research is to use advanced statistic methods and econometric model in determining the value of economic and trade relation between Russia and Turkey, moreover, the effect of these countries upon each other’s. In order to get in to the accurate details of this relation value, it would be necessary to focus on some data(1989-2015) as a support for these variables: (Growth domestic product, export, and import). This research includes there parts which are: the economic summary about the Russia and Turkey, the supports that develop the relations between these countries (as theoretical aspects of the research), study and analysis between both countries in economic relation( as a practical aspect of the research). The most important result that this research concludes is that the trade exchange between both countries reached 33 billion dollars. This trade exchange includes (export and import which are oil and natural gas) and tourism. Finally, the research suggests that: it is important to expand the economic relation between both countries in terms of cooperation strategy, and Russia must see Turkey as place for a great market in Oil and natural gas, in order to keep their relations stronger, both must be in peace economically and politically and solve the any conflict or contradiction may happen between them.